Spiro-Lactams as Novel Antimicrobial Agents - Alves, Américo J. S. (2020)
Introduction: Structural modulation of previously identified lead spiro-β-lactams with antimicrobial activity was carried out. Objective: The main objective of this work was to synthesize and evaluate the biological activity of novel spiro-lactams based on previously identified lead compounds with antimicrobial activity. Methods: The target chiral spiro-γ-lactams were synthesized through 1,3-dipolar cycloaddition reaction of a diazo-γ-lactam with electron-deficient dipolarophiles. In vitro activity against HIV and Plasmodium of a wide range of spiro-β-lactams and spiro-γ-lactams was evaluated. Among these compounds, one derivative with good anti-HIV activity and two with promising antiplasmodial activity (IC50 < 3.5 µM) were identified. Results: A novel synthetic route to chiral spiro-γ-lactams has been established. The studied β- and γ- lactams were not cytotoxic, and three compounds with promising antimicrobial activity were identified, whose structural modulation may lead to new and more potent drugs. Conclusion: The designed structural modulation of biologically active spiro-β-lactams involved the replacement of the four-membered β-lactam ring by a five-membered γ-lactam ring. Although conformational and superimposition computational studies revealed no significant differences between β- and γ- lactam pharmacophoric features, the studied structural modulation did not lead to compounds with a similar biological profile. The observed results suggest that the β-lactamic core is a requirement for the activity against both HIV and Plasmodium.